Z dziejów sowieckich obozów dla Polaków z Wileńszczyzny: łagier nr 0321 w Jełszance koło Saratowa - Rogut, Dariusz (Acta Universitatis Lodziensis. Folia Historica, 2001)
The operation „Ostra Brama” („sharp Gate") was begun within the frame of „Burza” („Storm”) action in Wilno district at night on July 6th to 7th 1944. The aim of operation was to liberate Wilno by the forces of the Polish Home Army before the soviet troops would come. This attempt failed. The USRR regarded Home Army as an „enemy structure” and greater part of Polish detachments were disarmed by Soviets. Arrested Polish soldiers were deported to lagiers (soviet camps in Gulag system). The massive repression were undertaken against the Poles all over Wilno district. The Poles suspected to participated in the „Polish counter-revolutionary organisations” were deported to the „filter” camps (PFL). There they were investigated to find those soldiers of Home Army who still were not captured. In 1945 one of the group of the arrested – 2242 persons (mainly the Poles) - was transported in two parts to PFL No 0321 in Jelszanka near Saratow. The prisoners (men and women) were used for digging the ditches for the gas main Saratow-Moskwa, or for various works in kolkhozes and building operations. Extremely hard work, tragic sanitary conditions and the lack of medicines caused high death rate among the Poles. Probably about 150-200 persons died. Some relase of prisoners in August 1945 was limited mainly to those completely unable to work, because of the exhaustion and destruction of their health. Still the other camps waited for the rest of the Poles. In October 1945 they were sent to PFL No 0331 in Kutaisi in Georgia. They were to be stay there for following two years. After the revolt of prisoners in Kutaisi (May 1947) the Poles were divided into three groups and sent to the camps in Borowicze (No 270), in Astrachan, and in Stalingrad (No 108). Most of them were released not earlier than on the turn of 1948/1949.